ISOLASI, IDENTIFIKASI, DAN KARAKTERISASI BAKTERI ASAM LAKTAT DARI DADIH SUSU KERBAU - sunaryanto, rofiq; marwoto, bambang (Jurnal Sains dan Teknologi Indonesia, 2012)
Dadih is one of the traditional fermented milk products of West Sumatera. Dadih contain a lot of lactic acid bacteria that acts as a coagulant and preservative. Some lactic acid bacteria also act as a probiotic agent because of characteristics that are resistant to acidic conditions. Some of the main requirements of microbes that can be used as probiotic microbes were resistant to low pH, bile salts, able to colonize, and having antimicrobial activity. Each species of the genus Lactobacillus havedifferent characteristics. This characteristic are influenced by the environment in which the bacteria live. Isolation, identification and characterization of lactic acid bacteria derived from buffalo milk were done. The results of isolated lactic acid bacteria was Lactobacillus plantarum. The characterization of Lactobacillus plantarum indicated that these isolates were able to survive in a concentration of medium containing 0.5% bile salts, resistant to acidic media until pH 2, have antimicrobial activity (inhibit Escherichia coli, Staphylococcus aureus and Enterococcus faecalis).